Preparation and Mechanism Analysis of Boiling Resistance of the Fresh Alum-Free Sweet Potato Vermicelli Containing Gliadin Fractions - Tingting Liu; Zhifang Men; Changjiangsheng Lai; Xijun Lian (Foods)
Alum, an essential additive in sweet potato vermicelli (SPV) production, is harmful to health. To eliminate the harm to the human body caused by alum in sweet potato vermicelli, and considering the different viscous properties of gliadin fractions, an experiment was performed to replace alum with gliadin fractions to enhance the boiling resistance of SPV in this study. The results showed that the longest boiling-resistant time of fresh SPV extended to 34.31 min when swelling the dough binder at 50 °C for 5 h, adding a 2% complex of ω-gliadin + αβγ-gliadin at a ratio of 1:1, and mixing at 70 °C for 20 min. The result was 95.7% higher than in the control. Starch swelling and freeze–thaw processes could partially replace the role of alum in preparing SPV. The results of FTIR and 13C solid-state NMR showed that the esterification reaction of ω-gliadin and αβγ-gliadin and hydrogen bonds between sweet potato starch and gliadin fractions reinforced the boiling resistance of vermicelli. There was no ordered area of starch in the new water-resistant vermicular. The gliadin fractions formed crystal with a diffraction angle of 17.38° (3.25 Å). Long-term cold storage could improve the boiling resistance of fresh sweet potato vermicelli. Additionally, the short-term retrogradation of sweet potato amylose significantly reduces its boiling resistance. The study provides new primary data and theoretical support for the industrial application of alum-free fresh sweet potato vermicelli.